2000
DOI: 10.1023/a:1005140927442
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The purpose of this study was to investigate the temporal unfolding of local acoustic information and sentence context using both cross-modal interference (CMI) and word-monitoring tasks. The timing of sentence context effects have important theoretical implications for models of language processing (e.g., initial context independence vs. initial interaction). Yet, different tasks tend to yield different results. For both experiments, stimuli from an acoustically manipulated "goat-to-coat" continuum were embed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The contrast between subject–verb agreement and reflexives is striking since retrieval for both dependencies targets the same structural position, i.e., the subject of the local clause. These findings are important because they cast doubt upon the claim that all linguistic dependencies are uniformly resolved using an error-prone retrieval mechanism, as suggested in previous research ( McElree, 2000 ; McElree et al, 2003 ; Lewis and Vasishth, 2005 ).…”
Section: Introductionmentioning
confidence: 57%
“…The contrast between subject–verb agreement and reflexives is striking since retrieval for both dependencies targets the same structural position, i.e., the subject of the local clause. These findings are important because they cast doubt upon the claim that all linguistic dependencies are uniformly resolved using an error-prone retrieval mechanism, as suggested in previous research ( McElree, 2000 ; McElree et al, 2003 ; Lewis and Vasishth, 2005 ).…”
Section: Introductionmentioning
confidence: 57%
“…In some studies the task was attentive listening (Obleser & Kotz, 2010; Obleser et al, 2007), while in other work subjects were asked to determine retrospectively whether a particular word occurred in the sentence (Davis, Ford, Kherif, & Johnsrude, 2011). A study by Guediche and colleagues (Guediche, Salvata, & Blumstein, 2013) took a different approach, manipulating word initial VOT in otherwise clear speech to create potential lexical ambiguity as in the behavioral studies of Connine (1987) and Borsky et al (2000). Consistent with the behavioral literature, the studies of Davis et al (2011) and Guediche et al (2013) showed the strongest sentential context effects on phonemic interpretation for speech that was either phonetically ambiguous or moderately degraded by noise vocoding.…”
mentioning
confidence: 93%
“…Abada, Baum, & Titone, 2008; Boothroyd & Nittrouer, 1988; Borsky, Shapiro, & Tuller, 2000; Borsky, Tuller, & Shapiro, 1998; Connine, 1987; Connine, Blasko, & Hall, 1991; Kalikow, Stevens, & Elliot, 1977; G. A. Miller, Heise, & Litchen, 1951; G. A.…”
mentioning
confidence: 99%